MENINGKATKAN DAYA SAING PERUSAHAAN CAREGIVER MELALUI WAWANCARA VIDEO SEBAGAI STRATEGI BRANDING DIGITAL - Rizaldi Putra; Memet Sanjaya; Lambok Rommy Sulaeman; Ade Oki Pebiansyah; Deni Utama; Berliana (JURNAL PENGABDIAN MANDIRI, 2025)
The caregiver industry plays a vital role in providing healthcare services amidst the increasing ageing of the global population. However, intense competition requires companies to innovate in marketing strategies. This research explores the use of video interviews as part of a digital branding strategy to enhance the competitiveness of caregiver companies. Through video interviews, companies can deliver authentic narratives that build credibility and emotional connections with audiences. The results show that video interviews not only enhance brand image, but also create significant differentiation in the market. Video content featuring testimonials from customers and labour professionals helps strengthen public trust in the services offered. In addition, video interviews increase digital interaction and reach, allowing companies to better connect with audiences. The findings confirm that innovative digital branding strategies, such as video interviews, can provide a sustainable competitive advantage for caregiver companies. As such, companies are advised to integrate video-based content in their marketing strategies to stay relevant and compete in a dynamic market